Topographic recording of the Slalom racing route in snow - V.F. Giovanis; F.A. Yiaghis; P.V. Vasileiou (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: The purpose of the present research was the study and evaluation of the theodolite's (topographic speedometer) use in tracing a path in slalom racing on snow conditions with 58 gates and also to record the optimal method of tracing a slalom route in relation to: a) the "velocity" of the race track (degree of difficulty of slalom), b) safety of tracing the slalom route. Methods: This research was based on methodology and measurements of a race track in giant slalom with 35 gates in the ski resort "3-5 Pigadia" of Naoussa - Greece. The topographic speedometer was fixed in place at the start of the route. From this point, measurements were taken, for the placement of all 58 gates throughout the route. The measurement was taken using the pole-prism, placed in each interior gate turn, at which the theodolite was aimed. With the help of topographic speedometer the following geometrical parameters have been registered: distance between the gates (Δs), altitude difference of points (Δh) with an accuracy up to 1cm, terrain slope (θ), gate angular deviation (δ) with an accuracy of up to 1 minute of the angle (°). This allows the creation of the top-view, side-view (profile) and three-dimensional aspect of the track, under race conditions on snow and not on dry ground. Results: The correlation coefficient (r) between the geometry factor (V.gs) and average the above geometry parameters had the following respective values: V.gs -Ms = 0,15, V.gs -Mθ = - 0,52, V.gs -Mδ = - 0,29 for 58 gates on a level of statistical significance of p < 0,05. Conclusions: The first part comprised of 10 gates was the "fastest" (V.gs = 18 degrees) of the total slalom route in Naoussa with 58 gates (V.gs = 14 degrees). With the above criteria, slaloms will be compared to each other and will be evaluated against age and safety.